Effectiveness of Strategic Management Practices on Governance of Local Government Authorities in Tanzania - Pandisha, Haghai; Kombe , Wilbard; Kayunze , Kim (European Journal of Business and Strategic Management, 2023)
Purpose: Adoption of Strategic Management Practices play a significant role in improving governance of Local Government Authorities and enhances good service deliverance at grassroot level. The Local Government and Central Government have been working collating to ensure that staffs are committed to implement strategic management plan. The results of this study will help practitioners, policy maker's government staff and appointed leaders to opt corrective decisions in formulation, implementation and evaluation of strategic plan of the council. This could result into achievement of the council goal and hence performance improvement. Methodology: The study used content analysis and non-parametric analysis to determine the significant changes in accountability and transparency before 2015 and during the 2015/2020. Mixed methods approach were adopted where simple random sampling was used to obtain sample size using Israel formula and purposive sampling was to obtain key informants for interview. Multiple methods were used to collect data and triangulate the information for reporting the findings of the cases obtained in the study area. Quantitative data were mainly collected through questionnaire from sample size of 351 respondents (85%), interview method used to collect data from 63 (15%) key informants and documentary review was used to triangulate and acknowledge the cases emerged from the study findings. Data were analyzed using IBM SPSS v.20. Findings: Governance of Local Government Authority was measured by assessing accountability, strategic plan, implementation plan, monitoring and evaluation, specialization, work plan delivered, council chart, transparency and planning linked with and budgeting. It is recommended that trainings, implementation sensing, follow-ups, efficient working resulted to efficient Strategic Management Practices and achievement of council overall goal. The study experienced a significant improvement in both accountability and transparency in 2015-2020 implementation of strategic plans based on estimated budget by the Council. Unique Contribution to Theory, Practice and Policy: The study recommend that a written strategic plan should be referenced by staff in ensuring implementation of the assigned duties to achieve the stated objectives based on planned activities and resources allocated with maximum commitment to all departments.